The Impact of the Degree of Risk-Sharing in Health Financing on Health System Attainment - Carrin, Guy (World Bank, Washington, DC, 2013)
A simple econometric analysis is undertaken concerning the impact of the degree of risk sharing in countries' health financing organization on the goals of the health system, as defined in the World Health Report 2000, i.e., the level of health and its distribution across the population, the level of responsiveness and its distribution across the population, and fair financing. The degree of risk sharing varies according to whether countries have a universal coverage system, financed via social health insurance or general taxation, or systems with less well-developed coverage including variants of social health insurance and/or general taxation benefiting specific population groups. The research undertook a classification of countries according to the degree of risk sharing, based primarily on the health care financing legislation of the World Health Organization's 191 member states and on its data base of Health System Profiles. The results obtained give empirical support to the hypothesis that the degree of risk sharing in health financing organizations impacts positively on health system attainment, as measured by the five goals indicators.